1996
DOI: 10.1017/s0963180100006733
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Arguments for and Against Euthanasia and Assisted Suicide: Part One

Abstract: In advanced technological societies there is growing concern about the prospect of protracted deaths marked by incapacitation, intolerable pain and indignity, and invasion by machines and tubing. Life prolongation for critically ill cancer patients in the United States, for example, literally costs a fortune for very little benefit, typically from $82,845 to $189,339 for an additional year of life. Those who return home after major interventions live on average only 3 more months; the others live out their day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Respect for a patient’s autonomy is considered an essential bioethical principle (Ersek, 2004; Thomasma, 1996). An autonomous decision is a decision that is made freely and in full knowledge and understanding of the information necessary to make such a decision.…”
Section: The Issue Of Autonomymentioning
confidence: 99%
“…Respect for a patient’s autonomy is considered an essential bioethical principle (Ersek, 2004; Thomasma, 1996). An autonomous decision is a decision that is made freely and in full knowledge and understanding of the information necessary to make such a decision.…”
Section: The Issue Of Autonomymentioning
confidence: 99%
“…Although some philosophers debate the distinctions between palliating and killing, or the principle of double effect (Cavanaugh, 1998;Thomasma, 1996Thomasma, , 1998, dialog with these nurses showed that they viewed killing as wrong or "evil." April thought her Roman Catholic roots had influenced her aversion to any action that might prematurely end life ("life at any cost").…”
Section: Fine-tuning Dyingmentioning
confidence: 99%
“…the urgency of considering issues for patients who increasingly fear that their final wishes will not be honored and thus be forced to suffer unnecessarily (Capron, 1996;Thomasma, 1996).…”
Section: Journal Of Gerontological Social Work 50mentioning
confidence: 99%
“…Some of the strongest opposition of physician-assisted suicide center around the Hippocratic oath of physicians to ''do no harm,'' which prohibits the prescription of lethal doses of medications to patients. The relief of pain, most often seen as a primary reason for requesting euthanasia or assisted suicide, should be administered through standard medical care, with the recognition that increased education regarding pain management and hospice care among physicians may be needed (Brody, 1992;Capron, 1996;Quill, Cassel, & Meier, 1992;Thomasma, 1996).…”
Section: Definitions and Current Debatementioning
confidence: 99%
See 1 more Smart Citation